Haemoglobin D Trait-An Uncommon Haemoglobinopathy in Chattogram: A Case Report - Sultana, Razia; Gosh, Tani (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
This case presents haemoglobin D Trait (Hb-D) which is a rare disease in Bangladesh. It is a heterozygous state for haemoglobin D who came to Laboratory Medicine Department of Chattogram Maa Shishu-O-General Hospital (CMSOGH) for heamoglobin electrophoresis. Our patient was 9 years old girl from Noakhali, Bangladesh. She was clinically silent with no splenomegaly. Her peripheral blood film was microcytic hypochromic anaemia and Capillary Electrophoresis (CE) of Hb revealed Hb D Trait. On family screening her father was Hb E trait, mother was Hb D trait and younger sister turned out normal Hb study. Compound heterozygosity for haemoglobin D and haemoglobin E may be present in subsequent pregnancy of her mother. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 81-83